Diversion and recidivism: Salt Lake Peer Court unsettling racial and ethnic disparities - Owen, Rebecca Y. (Journal of ethnicity in criminal justice, 2025)
Youth courts are a diversion program steering first-time, justice-involved youth away from the juvenile justice system. A comparison of recidivism outcomes between Salt Lake Peer Court (SLPC) and Juvenile Court referred youth during 2010 – 2016, shows that individual characteristics affected recidivism more than legal factors after controlling for participation in and completion of the SLPC diversionary program. Also, the racially diverse samples allowed for an examination beyond the problematic White/Black binary. The varied significant effects for race/ethnicity suggest the potential of peer courts for unsettling diversion disparities among justice-involved youth.